2016
DOI: 10.1049/iet-pel.2015.0559
|View full text |Cite
|
Sign up to set email alerts
|

Impedance interactions in bidirectional cascaded converter

Abstract: A cascaded converter is built by connecting one elementary converter to another. Output impedance of one converter will therefore interact with input impedance of the other converter. This interaction will change when power flow reverses. To compare this difference, an investigation is performed here for showing that forward and reverse interactions are prominently different in terms of dynamics and stability, even though the cascaded converter control remains unchanged. The concluded findings have been verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Despite the above merits, the DAB-based two-stage converter suffers from unstable problems. Similar instability issues have also been reported in [7]- [9]. The stability criteria for unidirectional two-stage converters have been proposed in [10]- [12].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Despite the above merits, the DAB-based two-stage converter suffers from unstable problems. Similar instability issues have also been reported in [7]- [9]. The stability criteria for unidirectional two-stage converters have been proposed in [10]- [12].…”
Section: Introductionsupporting
confidence: 64%
“…It has been found that the stability of the bidirectional two-stage converter is related to its control strategy. When the power is transferred from the voltage controlled sub-converter to the current controlled sub-converter, the bidirectional two-stage converter may be unstable [9].…”
Section: Introductionmentioning
confidence: 99%
“…To study the effects of proposed stabilization, measurements of Z in from the full order nonlinear simulation model have been performed, as commonly done by other researchers as well (see e.g. [46]). As discussed in Section II-B, measurement of frequency responses is a standard approach to study the dynamic behavior of complex nonlinearities for which such response is difficult to analytically calculate (e.g.…”
Section: A Dc-link Stabilitymentioning
confidence: 99%
“…But the implementation of the method in [18][19] is complicated. In [20], the DC impedance characteristics of the dual active bridge (DAB) Inverter cascaded system were analyzed, and the impedance interaction between DAB and the inverter, caused by different power flow directions, may result in instability in the cascaded system. Similarly, in [21], a DC-AC cascaded system was used as a topology to study the effects of bidirectional power flow on DC impedance characteristics.…”
Section: Introductionmentioning
confidence: 99%